Penggunaan Puzzle Pada Masa Pandemi Covid-19 Sebagai Alternatif Peningkatan Kemampuan English Vocabulary Siswa SD di Desa Putukrejo Kabupaten Nganjuk - Toyyibah; Fira Fachruli Aulia (Abdimas Indonesian Journal, 2021)
Vocabulary is an important thing in a language. It is not only important in Indonesian, but also in English and even other languages. English which in fact is a foreign language makes this subject still feared by elementary students. They think that English is difficult, so an approach and introduction must be done first. The introduction must also be gradual, especially in elementary school-aged children and even at an early age. This study aims to determine the English language skills of elementary school students in Putukrejo Village using puzzle media. During the current pandemic, students' English skills may decrease due to the lack of material delivered by the teacher and only teaching and learning activities through gadgets without face-to-face learning, so this research is expected to be able to improve students' English skills, especially in the part of body vocabularies. The method used in this research is descriptive qualitative and involves 6 samples of elementary school students in Putukrejo Village. The results of this study indicate that 4 samples from a total of 6 samples are considered to have fairly good English skills and 2 samples are considered to be lacking in mastering English, which material is part of the body vocabularies. Students are given a puzzle which contains pictures of body parts and the names of body parts that have been scrambled and cut out by the researcher. There are three stages carried out by the researcher, namely: the introduction of vocab (part of body vocabularies), the testing stage using puzzles, and finally doing reflection using the Simon Says game.